Phytochemical study of Lantana camara flowers, ecotoxicity, antioxidant, in vitro and in silico acetylcholinesterase: molecular docking, MD, and MM/GBSA calculations - da Fonseca, Aluísio Marques; Luthierre Gama Cavalcante, Antônio; Mendes, Antônia Mayara dos Santos; da Silva, Francisco Danilo Ferreira Costa; Ferreira, Débora Cristina Lima; Ribeiro, Paulo Riceli Vasconcelos; dos Santos, José Cleiton Sousa; dos Santos, Hélcio Silva; Gaieta, Eduardo Menezes; Marinho, Gabrielle Silva; Colares, Regilany Paulo; Marinho, Emmanuel Silva (Journal of biomolecular structure & dynamics, 2023)
Lantana camara L. (Verbenaceae), commonly called lead cambará, has often been used in folk medicine as antiseptic, antispasmodic, against hemorrhages, flu, colds, and diarrheic. This plant is considered a weed and an ornamental and medicinal plant and is an essential source of natural organic compounds, mainly flavonoids. This work aims to investigate the chemical composition and evaluate the biological properties such as antioxidant and acetylcholinesterase of the constituents from L. camara flowers. In addition, the computational simulation was carried out with the constituents identified. The results showed that methanolic extract of the flowers of L. camara presents toxicity, antioxidant activity with 97.8% inhibition percentage in the concentration of 0.25 mg mL −1 against the DPPH radical, and acetylcholinesterase activity. The phytochemical study of extract from L. camara flowers resulted in LC-MS identification of 18 polyphenolic compounds, such as phenolic acid derivatives, phenylethanoid glycosides, and flavonoids. In the in silico study, flavonoid isoverbascoside showed affinity energy of −9.9 kcal.mol −1 with the AChE enzyme. Their phytochemical content, mainly the presence of flavonoids and phenolic compounds in L. camara extracts, may be related to the antioxidant and anticholinesterase potential observed. Communicated by Ramaswamy H. Sarma